On the influence of nonlinearities on vibrational energy transduction under band-limited noise excitations. (September 2016) - Nakano, K; Su, D; Zheng, R; Cartmell, M
Abstract: Vibrational energy harvesters are often excited by band-limited noise excitations. In this paper, the influence of the stiffness nonlinearity on the transduction of the energy harvester and the relative performance of linear, monostable hardening-type and bistable energy harvesters are compared and investigated. The performance is experimentally compared under band-limited noise excitations of different levels, bandwidths, and centre frequencies at first. The rms output power delivered to the same load resistance is measured and compared under the same excitation levels, which indicts the constant electrical damping level. It is shown that the effect of nonlinearities is strongly dependent on the excitation parameters. Under a moderate excitation level it is shown that the monostable hardening-type oscillator performs worse than its linear counterpart under band-limited excitation. However, the results also illustrate that for the most part of the frequency and bandwidth range considered, the bistable harvester can outperforms the linear variant but for around the peak output area. Moreover, the comparison is also numerically conducted with the consideration of the optimised electrical damping level and the displacement constraint of the device. General conclusions are drawn based on the experimental observations.